2021
DOI: 10.1002/eap.2256
|View full text |Cite
|
Sign up to set email alerts
|

Host contribution to parasite persistence is consistent between parasites and over time, but varies spatially

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…One possibility is that Bd and Rv (which were first detected in 2005) caused declines in the most susceptible species before systematic monitoring of populations began (monitoring started in 2007). The common midwife toad, A. obstetricans , is known to be important in the persistence and spread of both Bd and Rv in amphibian communities ( 23 , 30 ). If their populations were reduced significantly before 2007, their role in the transmission of Bd infection to other species could have been greatly reduced, and hence the impact of Bd on sympatric species could have significantly reduced, which is consistent with the lack of strong association between the presence of Bd and mass mortalities or population decline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One possibility is that Bd and Rv (which were first detected in 2005) caused declines in the most susceptible species before systematic monitoring of populations began (monitoring started in 2007). The common midwife toad, A. obstetricans , is known to be important in the persistence and spread of both Bd and Rv in amphibian communities ( 23 , 30 ). If their populations were reduced significantly before 2007, their role in the transmission of Bd infection to other species could have been greatly reduced, and hence the impact of Bd on sympatric species could have significantly reduced, which is consistent with the lack of strong association between the presence of Bd and mass mortalities or population decline.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, when no moribund Alytes tadpoles were present in the water, adult I. alpestris exhibited less severe and less frequent signs of ranavirosis (J. Bosch, personal observations) despite Rv infection being persistent in the species. Over-wintering larvae are known to be an important host for many infectious pathogens, including Bd and Rv ( 23 , 39 41 ), and so perhaps with a reduction in their abundance other species can benefit from more breaks in the chain of initial transmission and subsequent re-infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of locationspecific dominant animal reservoirs and their transmission contributions to humans, along with model calibration to local data are evidently crucial (27,28). Quantifying each host's contribution to transmission enables the identification of maintenance and essential hosts, and the predicted impacts of control strategies targeting these hosts (29,30,31). It has been shown that human-only treatment is insufficient to achieve EPHP because transmission is maintained by untreated reservoirs.…”
Section: Pillar I: Epidemiologymentioning
confidence: 99%